An investigation of the relations between stress and prospective memory. Issue 2 (17th February 2020) - Stewart, Brandon T.; McFarland, Craig P.
ABSTRACT: Prospective memory (PM), or remembering to perform intentions in the future, has important implications for one's daily functioning and quality of life. Another common human experience is stress. Despite the significance and ubiquity of both PM and stress, our understanding of the relations between them is limited. The aim of the current study was to further delineate the relations between acute stress, chronic stress, non-focal event-based PM, and time-based PM. The results of the study revealed that acute stress induction after PM intention formation did not contribute to differences in non-focal event-based PM performance or time-based PM performance. However, self-reported chronic stress was significantly correlated with enhanced monitoring and time-based PM. In the present study, participants may have had optimal levels of enduring stress that contributed to enhanced monitoring behaviour (i.e. the prospective component of PM) and the ability to complete time-based intentions.